A study on energy separation mechanism in Ranque-Hilsch vortex tube - Mohd Hazwan, Yusof (2015)
A vortex tube (VT) is a simple and useful fluid dynamic device, used to obtain both cold and hot flows from compressed gas at room temperature. It can produce a cold flow measuring around —30'C, and a hot flow of up to around 130'C. Until now, the theory and model analysis of the energy/temperature separation inside of VT is proposed by a number of researchers. From those theories, it is generally accepted that the generation of the cold flow is caused by an adiabatic expansion, which occur after a compressed gas flows through an inlet nozzle. However, details about the physics of the cold flow generation, from the fluid dynamics view point still remain unclear. The objective of this study is to clarify the energy separation mechanism (ESM) of VT. Therefore, in order to accomplish this objective, experimental and analytical studies were carried out. In order to clarify the flow structure of the cold exit flow, the total temperature and Pitot pressure of a cold flow center were measured. In addition, two simple flow visualization techniques were used to observe the reversed flow at the cold exit. The mixing temperature of cold and hot flows were also measured to clarify the performance of VT used in this research. In Chapter 1, the basic idea about a VT, such as its history, the types, the example of usage, and the advantages/disadvantages of a VT is introduced. A proposed flow pattern inside a Counter-flow VT is also explained. In the literature section, the researches on the geometrical optimization of the VT, and the flow pattern inside a VT are included with a discussion on the contrary points of the researches. The objectives of this thesis are also described in this chapter. Chapter 2 describes the experimental apparatus and procedures of the total temperature/pressure measurement methods, and the flow visualization techniques. The specifications of the equipment and measurement devices are shown in this chapter. There are two simple flow visualization techniques. Both techniques use needle and oil paint droplet. The first technique uses an oil paint droplet, on a 0.75mm-diameter needle. The oil paint droplet on the needle is positioned along the centerline of the cold flow. The movement of the oil paint droplet represents the flow direction of the cold flow. Another technique uses a 0.70mm-diameter needle with 10 small holes which can exudate colored oil (exudation needle). The exudation needle is inserted into the cold flow along the centerline. Then the colored oil is injected to the exudation needle little by little and exuded from the small holes. The flow direction of the colored oil on the exudation needle represents the flow direction of the cold flow. In Chapter 3, the development of total temperature probe with the objective and structure of the probe is explained. Those probes are named as Type 1, 2, and 3. An evaluation experiment is conducted using the Type 1, 2, and 3 to determine the effects of probe angle along the centerline of a sonic jet nozzle on the measurement accuracy. Results show that the largest measurement error for Type 1, 2, and 3 are —1.3°C, —1.1°C, and —0.7°C, respectively. From these results, the effect of the angle of the thermocouple on the total temperature measurement is negligibly small. Chapter 4 reports the results of total temperature/pressure measurements and flow visualization at cold exit. The experiments of the effects of the cold fraction on the measurement were carried out with the Type 3 total temperature probes and Pitot pressure probe. From the results, a negative and positive gauge pressure regions are measured. It implies the possibility of a direct/reversed flow at the cold exit. To clarify the flow direction, two kinds of flow visualization are conducted. The flow direction of the cold flow is determined by the movement of the oily paint droplet. From the results, a reversed flow is observed around the center of cold exit at a smaller cold fraction. The length of reversed flow increases as the cold fraction decreases, which implies the decrease in the pressure at the core of the vortex chamber. A lower pressure in the vortex chamber means a lower static/total temperatures at the core of vortex chamber and a higher static/total temperatures at the outer region of the vortex in the vortex chamber. This is the effect of cold fraction on the EMS at an arbitrary inlet pressure. When the inlet pressure increases at an arbitrary cold fraction, the tangential velocity increases, which results in a lower static/total temperatures at the core of the vortex chamber and a higher static/total temperatures at the outer region of the vortex in the vortex chamber. Chapter 5 describes a mathematical model analysis of compressible vortex flow with a review of some literatures. The basic equations, the laminar vortex solutions, turbulent vortex solutions, and problems with VAB model are explained. The improvement of the VAB model is conducted by replacing the laminar Prandtl number with a laminar plus turbulent Prandtl numbers. The results show that the total temperature is roughly independent of the summation of laminar and turbulent Prandtl numbers. The EMS in a turbulent compressible vortex is discussed and proposed, by examining the VAIB model. The results show that a hotter gas in the peripheral region of the vortex is mainly caused by heat generated by viscous dissipation, and colder gas in the vortex core is mainly generated by viscous shear work done on the surface of the fluid element to the surrounding gas. Finally, the conclusions of this study based on the implementation of objectives are summarized in Chapter 6.